PENGARUH PEMBIAYAAN MACET TERHADAP PENYALURAN DANA BERGULIR PADA UNIT PENGELOLA KEGIATAN (UPK) KECAMATAN SEMPARUK - Tasa Melyanti; Iwan Kusnadi (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
This study aims to find out the distribution of revolving funds in the activity management unit (UPK) of Semparuk District, this study uses a quantitative approach, namely a research approach that uses quantitative data or data in the form of numbers. The quantitative research approach can be interpreted as a research method based on the philosophy of positivism, used to examine certain populations or samples, data collection using research instruments, established hypotheses. The results of this study are that Based on the results of research and discussion on the analysis of the effect of bad financing on the distribution of revolving funds, conclusions can be drawn, namely based on the test results on the variable of bad financing (X) partially, shows that there is no positive and significant relationship between bad financing and revolving funds in UPK Semparuk District and there is an effect of bad financing on the distribution of revolving funds in UPK Semparuk District by 7.8%.